PERGESERAN KONSUMSI PANGAN POKOK OLEH MASYARAKAT SUKU MOI DI DISTRIK SORONG TIMUR KOTA SORONG - Nebore, Indira R Yoku; Irbayanti, Diana N; Mamboai, Hans (Sosio Agri Papua, 2014)
The aims of this study to know a shift in the local staple food consumption patterns become staple food rice and the result purpose for know factors that a correlation with a shift in food comsumption . The basic method uses descriptive method, sampling is purposive sampling, sample taken from 15% at two district. Methods of processing and tabulation and analysis of data using the Spearman rank correlation. The results showed a shift in the local staple food consumption patterns become staple food rice with shifting levels of ≥ 66.68% - 100% which is high. The reason is because rice shift easily available, easily prepared, inexpensive and Moi tribal society already accustomed to eating rice. In each combination of food consumed, rice became the main option even respondents not satisfied, bullae not eat rice. Local staple food by Moi tribal society has a social function as the communication value and economic value. Based on the analysis of the Spearman rank test associated very strongly with income variable, while the numbers of familly members, formal education, staple food prices have a very weak and taste consumption of staple foods have a weak relationship to the fundamental shift in main food consumption.